Bayangan di ruang bayi: Menjelajahi lanskap psikologis baby blues - Rifa’ah, Hana Meliana (Maliki Interdisciplinary Journal, 2025)
For women, the pregnancy and postpartum experience is a precious one as it marks an important transition period in their lives. This period is characterized by hormonal and psychological changes that can trigger mental health issues, including baby blues syndrome, which manifests as extreme mood swings, anxiety and sadness after childbirth. Research has shown that emotional turmoil during this time can lead to deeper psychological problems, such as postpartum depression, if not treated promptly. The social stigma surrounding childbirth can exacerbate mothers’ inferiority complex, further affecting their mental health. The stages of adaptation experienced by mothers, from the phase of taking (dependence) to letting go (accepting new responsibilities), play a crucial role in their emotional well-being. Support from partners and family, in addition to interventions and education, can help alleviate baby blues symptoms. The quality of the mother’s mental health has a significant impact on the attachment between the mother and her children, which affects the child’s emotional development. Therefore, early intervention is crucial to ensure mothers and their children thrive during this critical time.